BORN TO CARE: GENDER ROLES AND EMOTIONAL OVERLOAD AMONG INFORMAL FEMALE CAREGIVERS - Barbas, Amanda Cavalcanti Pinheiro; Cobra, Bianca Lemos; Ferreira, Laleska Morais; da Silva, Lorena Lourenço Rosa; Souza, Mateus Henrique Oliveira; Ferreira, Melissa Mendes; Perez, Santiago de Matos Fernandes; da Silva, Tatiana Maria; de Sousa, Rosa Gouvêa (Seven Editora, 2026)
This is a study on understanding the impact of emotional and psychological overload on informal carers of home-based patients, with the aim of deepening this understanding based on determining factors such as the duration of care, the severity of the patient’s pathological condition, as well as their limitations and demands, the social support available and the coping strategies used by carers. In addition, the study seeks to understand how gender affects the mental burden of informal caregivers, observing this phenomenon from a social and scientific perspective. The methodological design involved content analysis of narratives by women caregivers in a community affiliated with a health unit in the interior of Minas Gerais. The findings showed that informal care, although essential for sustaining life and supporting family and community networks, remains structured on profoundly unequal bases. The caregivers interviewed revealed in their narratives that the daily practice of care is marked by gender, loneliness, and symbolic and spiritual strategies that function both as support and as a way of reframing suffering. In view of this, this study reaffirms that caregiving is also work, work that, when performed alone and continuously, causes illness. It is essential that care be understood as a collective responsibility and that progress be made.